The effect of carotid stenting on endarterectomy practice – A single institution experience. Issue 2 (April 2016) - Ali, A.; O'Callaghan, A.; Moloney, T.; Kelly, C.; Moneley, D.; Leahy, A.L.
Abstract: Objectives: The number of operations performed per surgeon is thought to determine the quality of carotid endarterectomy (CEA) surgery. The advent of carotid artery stenting (CAS) threatens to reduce the volume of CEA. This paper assesses CEA and the effects of the introduction of CAS service on outcomes. Design: Retrospective cohort study. Methods: Clinical data and results of CEA were reviewed retrospectively for the treatment of carotid stenosis, between January 1988 and December 2010. CEA patients were grouped into those treated before and after the introduction of CAS to our hospital in 2001. Results: 757 patients underwent a CEA between 1988 and 2010. The perioperative stroke rate prior to the introduction of CAS was 4.9%, and 3.3% after stent introduction in 2001. In this latter period, 85.5% had symptomatic stenosis which suggests that the patients were not low risk. The major adverse event rate (inclusive of death and myocardial infarction) post introduction of CAS from 2001 to 2010 was 4.1%. There was no correlation between post-operative stroke/MAE and procedure volume, despite the trend of decreasing CEA numbers over time. Conclusion: The introduction of carotid artery stenting has led to a decrease in carotid endarterectomy volume. However, outcomes in our high risk patient population are acceptable. Therefore, CEA remains the procedure of choice for carotid artery revascularization.